Structure of Escherichia coli After Freeze-Etching - Bayer, M. E. (1970)
Survival of Escherichia coli, quick-frozen under conditions similar to those employed for freeze-etching, is close to 100%. For determination of cell shrinkage, the diameters of freeze-etched E. coli cells (average, 0.99 μm) were compared with those of preparations after negative staining and after ultrathin sectioning. Negatively stained cells measured from 0.65 to 1.0 μm in diameter, and ultrathin sections showed average cell diameters of 0.70 μm. Freeze-etched replicas of logarithmically growing, as well as stationary, E. coli B cells revealed a smooth, finely pitted cell surface in contrast to cell surfaces seen with other preparative methods. The frozen cell wall may cleave in two planes, exposing (i) a smooth fracture face within the lipid layer and (ii) in rare instances an ill-defined particulate layer. Most frequently, however, cleavage of the envelope occurred between wall and protoplasmic membrane; large areas of the membrane were then exposed and showed a surface studded with predominantly spherical particles, an appearance which did not significantly change when the cells were fixed in formaldehyde and osmium tetroxide before freeze-etching. The distribution of these particles differed between logarithmically growing cells and stationary cells.